PROGRAM PEMBERDAYAAN MASYARAKAT BERBASIS RUKUN WARGA (PMB-RW) DI KECAMATAN RUMBAI PESISIR - Pujiyati "; Dadang Mashur (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
of this program starts by providing skills through training to the people who are targeted PMB-RW program. There are still many activities that have not been implemented in the PMB-RW program. In addition to the unfinished activities, activities that have been running was not optimal as planned. In addition, there are problems related to activities that should be prioritized. The activities that are carried out are still said to be activities that are not priority, due to the minimal budget. Not yet improve the social welfare of the economy and social that should be the objective of the PMB-RW Program in RumbaiPesisir District. Given the knowledge and skills in these various fields, it can be one of the capital for the community to create new jobs. The research was conducted using qualitative descriptive research method. This study uses the concept of program empowerment by Sujianto namely: Independence, Participatory, Networking, Justice, Sustainability. This research is data collecting technique which is observation, interview, documentation and literature study by using descriptive analysis technique. Community-based Community Empowerment (PMB-RW) Empowerment Program in RumbaiPesisir Sub-District has not been able to improve the economic, social, community, but the knowledge of the community who participated in the training has been obtained in the PMB-RW Program. Participation of escort personnel is already underway and has benefits for the running of the PMB-RW Program in planning and supervision. Public participation for the idea of activities has been running malaluimusyawarah network in the form of information, coordination, and communication. However, fund participation is still limited by the Municipal Government so that planned activities can not run all. The factors that affect the Community Empowerment Program Based on Citizens (PMB-RW) in RumbaiPesisir District is Participation in the form of funds and personnel / ideas in the form of ideas and justice. Funds for the implementation of activities that will affect the implementation so that the participation of counselors and ideas ideas go according to the wishes of the community. So that justice takes place in the Program Keywords: Empowerment, Program, Society